Rediseño geométrico de un resorte de ballesta para un vehículo de transporte de pasajeros Euro V (2024)
Suspension systems in vehicles play a fundamental role in improving comfort and safety while driving. However, in the case of Euro V type vehicles used in public transportation in Bogotá, specifically in the Integrated Public Transportation System (SITP), certain drawbacks have been identified in the performance of the leaf springs. These drawbacks have led to premature wear in some of the components of said springs.